Organic thin-film transistors based on conjugated polymer/carbon nanotube composites. (6th June 2007) - Gan, Ye; Li, C.M.; Zhang, Jie; Gamota, Dan
Thin film transistors (TFTs) were fabricated from poly(3-hexylthiophene) (P3HT)/carbon nanotubes (CNTs) composite as the active materials. Single walled CNTs were dispersed into a P3HT/chloroform solution. By drop casting, the composite solution was deposited onto the pre-fabricated device and formed a thin active layer for a TFT. The effect of different concentrations of CNTs on the charge carrier mobility of the composite was studied. A low ratio of CNT to the active material could significantly improve the carrier mobility while the on/off ratio was not reduced.